Phase composition of metallurgical zinc and lead slags = Skład fazowy żużli pochodzących z hutnictwa cynku i ołowiu - Adamczyk, Zdzisław; Nowińska, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Slags formed in the ?Miasteczko Śląskie? Zinc Smelting Plant process contain substantial amounts of heavy metals such as Pb, Zn, Cd, Cu. In hypergenic environment this elements may occur in stable or unstable phase. Environmental conditions and the forms of occurrence of elements decide about metals stability and mobility.
Keywords: hutnictwo cynku; hutnictwo ołowiu; żużle; środowisko hipergeniczne; iagramy Eh-pH; Zinc Smelting Plant; metals; slags; hypergenic environment; Eh-pH diagrams